The impact of surgery for trochanteric femur fracture on sexuality in men and their female partners. (20th November 2017) - Balci, Melih; Cankaya, Deniz; Tuncel, Altug; Yoldas, Burak; Guzel, Ozer; Senel, Cagdas
Purpose: This study was aimed to investigate the effects of trochanteric femur fracture treatment methods on erectile functions of the patients and on sexual functions with their female partners. Materials and Methods: A total of 43 patients with trochanteric femur fracture who underwent proximal femoral nail (PFN) or proximal femur locking compression plate (PF-LCP) surgery were included in the study. The PFN implant was applied to group 1 ( n = 23) and the PF-LCP implant to group 2 ( n = 20). All the patients and their female partners completed the 5-item version of the International Index of Erectile Function (IIEF-5) and the Female Sexual Function Index (FSFI) preoperatively and at 1 year postoperatively after the rehabilitation period. Results: The mean preoperative IIEF-5 and FSFI score was 21.910.9 and 21.911.1, 72.319.7 and 70.516.2 for the PFN and PF-LCP treatment groups, respectively, and at postoperative 1 year after rehabilitation, change in IIEF-5 score and FSFI score of each group was −6.512.1 versus −3.811.6, ( p < 0.001) and −16110.7 versus −6.314, ( p = 0.001), respectively. Conclusion: These data show that trochanteric femur fractures treated with PFN or PF-LCP had a negative impact on sexual function. PF-LCP had a greater negative effect than PFN on sexual function.